Myth or reality: the oxygen effect in rectal cancer radiotherapy - Dahbi, Zineb (Frontiers in Oncology, 2026)
BackgroundThe oxygen microenvironment plays a crucial role in tumor radio-sensitivity, influencing the effectiveness of radiotherapy. The oxygen effect, which increases radiosensitivity in the presence of oxygen, has been extensively studied but not fully understood. This study investigates the relationship between hemoglobin variation, a surrogate marker for tissue oxygenation, and survival outcomes, in patients with locally advanced rectal cancer treated with neoadjuvant radiotherapy.MethodsIn this retrospective study, we analyzed 97 patients with rectal adenocarcinoma treated with neoadjuvant pelvic radiotherapy between January 2016 and January 2024. Hemoglobin levels were measured before, during, and after radiotherapy, and hemoglobin variation (ΔHb) as a difference between maximum and minimum hemoglobin levels” was calculated. Active bone marrow (ABM) and low-density bone marrow (LDBM) were delineated for dosimetric analysis. Progression-free survival (PFS) was evaluated using Kaplan-Meier survival analysis, and the correlation between ΔHb, dosimetric data, and PFS was assessed using hazard ratios (HR) with a significance threshold of p < 0.05.FindingsThe median volumes of LDBM and ABM were 114.6 cc and 765.4 cc, respectively. The maximal doses received by LDBM and ABM were 54.2 Gy and 52.2 Gy. The incidence of grade 3 and 4 anemia was 8.21%, with a mean delta hemoglobin (ΔHb) of 0.75%. No correlation was observed with grade 1–2 anemia at any dose level. A significant correlation was found between grade 3–4 anemia, ΔHb, and V40 doses for both LDBM and ABM (p-value < 0.05). Patients with ΔHb ≤ 1.5 demonstrated significantly better progression-free survival (PFS) compared to those with ΔHb > 1.5 (HR = 0.65, p = 0.0013). Dosimetric analysis revealed that higher doses to both ABM and LDBM regions did not correlate with improved PFS outcomes, while hemoglobin variation was a critical factor influencing survival. These results emphasize the role of hemoglobin variation and oxygenation in enhancing radio-sensitivity, particularly in active bone marrow.InterpretationThis study provides evidence that hemoglobin variation significantly influences survival outcomes in rectal cancer radiotherapy, supporting the clinical relevance of the oxygen effect. Hemoglobin monitoring and oxygenation strategies could be integrated into clinical practice to improve treatment efficacy, especially when considering dosimetric impacts on contoured bone marrow regions (ABM and LDBM). Future prospective studies are required to confirm these findings and explore interventions aimed at optimizing tissue oxygenation during radiotherapy.